2001
DOI: 10.1016/s0020-7292(01)00392-7
|View full text |Cite
|
Sign up to set email alerts
|

A community based study on the change of practice of female genital mutilation in a Sudanese village

Abstract: This is the first community based study of FGM indicating a significant shift in practice between generations, young parents starting to question the value of FGM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
44
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 11 publications
11
44
1
Order By: Relevance
“…The current research provides support for the previously hypothesized motivations for FGC across cultures (Almroth et al, 2001;WHO, 2014), including the Igbo community. From an evolutionary perspective, FGC decreases men's paternity uncertainty by restricting women's sociosexuality-including women's desires to pursue extramarital relationships.…”
Section: Discussionsupporting
confidence: 80%
“…The current research provides support for the previously hypothesized motivations for FGC across cultures (Almroth et al, 2001;WHO, 2014), including the Igbo community. From an evolutionary perspective, FGC decreases men's paternity uncertainty by restricting women's sociosexuality-including women's desires to pursue extramarital relationships.…”
Section: Discussionsupporting
confidence: 80%
“…The girls in the current study were asked for reasons support the practice of FGM and they answered that circumcision is an important religious requirement, cultural and social traditional, restraining sexual desire, cleanliness for girls, chastity and evidence of feminist, in agreement with other studies (8,9,20) . Other studies in Africa concluded that the most significant factors associated with the acceptance of FGM were religion, tradition and social pressure, as reported in Egypt and Sudan (34,35) , while ethnicity and to control female sexuality were the most significant social predictor of FGM in Nigeria (36) . Both ethnicity and religion were the strongest predictors of FGM in the United Republic of Tanzania (37) .…”
Section: Prevalence Of Female Genital Mutilation Among School Girls Imentioning
confidence: 88%
“…In the current study, the most common post-practice complication were; bleeding, infection, pain, shock and injury to adjacent tissues, in agreement with others studies (4,8,40) .Recently, many articles have reported post-practice complications (early and late) such as severe pain, bleeding, incontinence, infections, mental health problems, sexual problems, primary infertility and difficult labour with high episiotomy rate. In addition, the repetitive use of the same instruments on several girls without sterilization can cause the spread of HIV and Hepatitis B and C (34,40) . The findings of the present study revealed that, the post-practice complications were more prevalent when the circumcision was performed by nurses or dayas, in agreement with other studies (5,41) .…”
Section: Prevalence Of Female Genital Mutilation Among School Girls Imentioning
confidence: 99%
“…In combination with other strategies, such as dress codes and limits on interactions between the sexes, FGM is perceived as an important guarantee that girls remain virgins until marriage. It thus also ensures the woman's marriageability (Almroth et al, 2001;Baker, Gilson, Vill, & Curet, 1993;Gruenbaum, 2001;Hicks, 1993;Missailidis & Gebre-Medhin, 2000;United Nations Population Fund (UNFPA), 1997;World Health Organization, 1986). The practice of FGM in these societies is thus intimately related to the status of women.…”
Section: Introductionmentioning
confidence: 99%